Literature Riview: Pengembangan Buku Cerita Bergambar Berbasis Discovery Learning untuk Meningkatkan Kemampuan Berpikir Kritis dan Keterampilan Proses Sains Siswa - Mazidah; Tri Ariani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The purpose of this study is to compile a systematic literature review to evaluate the effectiveness of the discovery learning model in improving critical thinking skills and science process skills among high school students. The importance of improving 21st-century skills, such as critical thinking skills (KBKr) and science process skills (KPS), is a major focus in education today. The Discovery Learning (DL) model is highly relevant because it places students at the center of learning, encouraging them to actively seek, analyze, and conclude their own findings. The method used was a systematic review of 50 scientific articles. These articles were searched for in the Publish or Perish and Spiece databases, with publication years limited to 2022 to 2025. The subjects of the study were research documents discussing the implementation of DL and the results of measuring its impact on high school students' critical thinking and science process skills. The results of the review concluded that the application of the discovery learning model has been proven to significantly improve high school students' critical thinking skills. In addition, the effectiveness of this model is optimized when combined with interactive teaching media, such as picture storybooks